Understanding User Behaviors in Social Networking Service for Mobile Learning: a Case Study with Twitter - Ha, Ilkyu; Kim, Chonggun (Malaysian Journal of Computer Science, 2014)
With the rapid adoption of smart devices, various services have been evolved in mobile environment. Particularly, Twitter has become one of major mobile social networking services. In spite of the increasing use of Twitter services by students and instructors in colleges, very little empirical studies that concern the impact of social media on the student learning environment have been published. In this paper, an experiment using Twitter is conducted for college classes to understand the effects on college student engagement and grades. The participants of experimental study comprise students of 2 college classes during one semester and only voluntary students attend this Twitter-based experiment. Network of Twitter using pattern such as community building, collaboration relationship and information sharing among students are analyzed. Some results about the relationships of seat positions, following patterns of Twitter and grades among students have been studied. By understanding the networking patterns among the students, we found that Twitter can play an efficient role of a mobile educational tool.